Optimization Of Arjowinangun Cadre Of Integrated Health Service - Erma Wahyu Mashfufa; Lilis Setyowati; Ollyvia Freeska Dwi Matra; Nur Aini (Jurnal Pengabdian Pancasila (JPP), 2024)
Cadre of Integrated Health Service are a community forum consisting of mothers working in the health sector to assist the Puskesmas screening program, reducing morbidity and mortality. The findings after FDG found that health training had never been carried out. This program aims to upgrade the knowledge and skills of Posyanda cadres to assist with puskesmas program tasks. Programs community service increase science and technology in the community with various programs: 1. Increasing the posyandu program for toddlers and older people to be more innovative, 2. Training and assistance with Basic Live Support (BLS) and emergency first aid (PPGD), 3 education on infectious diseases and how to handle them independently, 4 uses of natural ingredients to improve children's nutrition. Mentoring and training were carried out for four days. After the implementation of community service activities had a positive impact, Cadre of Integrated Health Service were able to help Community Health Center officers carry out screening to detect Non -communicable diseases.